2021
DOI: 10.32819/021021
|View full text |Cite
|
Sign up to set email alerts
|

Formation of spring barley productivity depending on seed inoculation with a biopreparation and foliar fertilization in the Steppe of Ukraine

Abstract: Scientifically substantiated application the elements of technologies with the use of microbiological preparations, macro- and microfertilizers, new growth regulators of plants of organic origin, allows not only to increase grain yields, improve its quality, but also to affect the economic efficiency of spring barley cultivation. Today, biological, growth stimulants are widely used in various types of agricultural crops. They are an effective method of achieving increased productivity, increasing resistance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, this process in Ukraine is a little bit slower than in the Western-European countries, as most researchers and agricultural practitioners are focused mainly on getting the best crop productivity.Therefore, soil tillage systems in this regard are mainly estimated from the point of view of nutrients accumulation and availability for plants, as well as formation of optimal agrophysical parameters for root growth and moisture uptake, while soil biology remains beyond the scope of scientific interest (Tanchyk et al, 2022). A very small number of Ukrainian studies focus on the features of soil microbiota and fauna to understand its ecological conditions, and an even smaller number of studies are devoted to the establishment of soil biological activity under the impact of modern agricultural practices (Ishchenko & Kozelets, 2021;Langraf et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, this process in Ukraine is a little bit slower than in the Western-European countries, as most researchers and agricultural practitioners are focused mainly on getting the best crop productivity.Therefore, soil tillage systems in this regard are mainly estimated from the point of view of nutrients accumulation and availability for plants, as well as formation of optimal agrophysical parameters for root growth and moisture uptake, while soil biology remains beyond the scope of scientific interest (Tanchyk et al, 2022). A very small number of Ukrainian studies focus on the features of soil microbiota and fauna to understand its ecological conditions, and an even smaller number of studies are devoted to the establishment of soil biological activity under the impact of modern agricultural practices (Ishchenko & Kozelets, 2021;Langraf et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Each of the trends has certain requirements for the grain properties, which for the malting barley are opposed to feed and food purposes of use (Fang et al, 2019;Guo et al, 2020;Rani et al, 2021). The most suitable for malting are "traditional" covered awned barley varieties (Laidig et al, 2017;Gamayunova et al, 2021;Habschied et al, 2021;Ishchenko & Kozelets, 2021). Great advances in malting barley breeding have been achieved in Western Europe, as well as in some other countries of the World (Edney et al, 2014;Matthies et al, 2014;Mastanjević et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the use of biological preparations, in particular, inoculants, biopesticides, regulators of growth of plants, microfertilizers, etc is an element of modern ecologically safe technologies for growing agricultural crops guarantees obtaining additional crops for small investments [4]. In particular, the results of research by a number of scientists [5] has showed that the treatment of spring barley seeds with the Vympel 2 plant growth regulator in combination with the use of Oracle microfertilizer contributed to the extension of the vegetation period of plants, an increase in their tilling ratio, an increase in their resistance to diseases and pests, and an increase in crop productivity.…”
mentioning
confidence: 99%